2017
DOI: 10.1016/j.ejphar.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nebulised magnesium sulphate on inflammation and function of the guinea-pig airway

Abstract: Magnesium sulphate is a potential treatment for acute severe asthma. However, the mechanisms and dose-response relationships are poorly understood. The first objective of this study was to examine whether inhaled magnesium sulphate exerts bronchodilator activity measured as bronchoprotection against histamine-induced bronchoconstriction in conscious guinea-pigs alone and combined with salbutamol. Secondly, we examined whether inhaled magnesium sulphate inhibits airways inflammation and function in models of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Several studies have shown that magnesium deficiency increases the production of many pro-inflammatory cytokines (such as TNF-α, IL-6) and that this effect is accompanied by the sensitization of cells such as neutrophils, macrophages and endothelial cells 14 , 17 , 24 26 . The development of cartilage injury-induced arthritis involves a series of immune responses that mobilize various types of immune cells into the wound site and activate host defences and tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that magnesium deficiency increases the production of many pro-inflammatory cytokines (such as TNF-α, IL-6) and that this effect is accompanied by the sensitization of cells such as neutrophils, macrophages and endothelial cells 14 , 17 , 24 26 . The development of cartilage injury-induced arthritis involves a series of immune responses that mobilize various types of immune cells into the wound site and activate host defences and tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Mg is established treatment of resistant asthma attacks [ 96 , 97 ]. Mg increases the effect of salbutamol [ 98 ] through inhibiting Ca 2+ influx by blocking the voltage-dependent calcium channels which then relaxes the smooth muscle [ 28 ]. Mg also has an immunoregulatory effect by reducing pro-inflammatory mediators and promoting synthesis of prostacyclin and nitric oxide which stimulates broncho- and vasodilatation [ 99 , 100 ].…”
Section: Biochemical and Clinical Manifestations Of Hypomagnesemiamentioning
confidence: 99%
“…Magnesium, an essential substance for basic biochemical reaction, participates in a cluster of normal physiological function and metabolism, such as the transport of potassium ion or calcium ion ( Flatman, 1984 ; Komiya and Runnels, 2015 ), energy metabolism, protein and nucleic acid synthesis ( Ohyama, 2019 ; Sissi and Palumbo, 2009 ). Magnesium also has anti-inflammation ( Abiri and Vafa, 2020 ; Eshraghi et al, 2015 ; Han et al, 2018 ; Kao et al, 2011 ; Ozen et al, 2020 ; Rochelson et al, 2007 ; Turner et al, 2017 ), anti-oxidation ( Güzel et al, 2019 ; Kao et al, 2011 ), anti-spasm ( Güzel et al, 2019 ; Yen and Thwaites, 2019 ), vasodilation ( Shimosawa et al, 2004 ; Wang et al, 2019 ), and neuroprotection ( Bachnas et al, 2019 ; Jameson and Bernstein, 2019 ). Therefore, magnesium homeostasis regulates reproductive system, cardiovascular system, digestive system, neurological system and respiratory system, etc, maintaining normal human health.…”
Section: Introductionmentioning
confidence: 99%